How the FTC May Reshape M&A Transactions by Banning Non-Compete Agreements - Lilli Johanknecht (Washington University Journal of Law and Policy, 2025)
Buyers to merger and acquisition transactions frequently utilize non-compete agreements that bind important employees who possess knowledge or skills integral to the business. The use of non-competes in this manner has prompted the Federal Trade Commission (FTC) to propose a controversial rule banning the use of most non-compete clauses. A final rule was later passed, and as written, includes several key employees to a seller’s business. While the FTC rule’s enforceability is in question, the prohibition on non-compete clauses will impact mergers and acquisitions in a transformative way. The FTC rule may have a significant detriment to capital mobility of buyers, not just in the clear employment context. The author notes the potential disadvantages, including losing business growth benefits, to the merger and acquisitions industry with adherence to the rule. In contracts, the author proposes that the FTC consider expanding the exceptions to the rule to include senior executives. A more effective solution combines state laws incorporating salary thresholds, reasonableness standards, and scope limitations. The FTC can still achieve a balance of protecting employees and the business interests of buyers.
Keywords: NonCompeteReform; FTCRegulations; MergersAndAcquisitions